Autonomous green house management system based on fuzzy-wireless sensor network - Naseer Sabri, Salim; Syed Alwee Aljunid, Syed Junid, Prof. Dr.; Mohd Fareq, Abd Malek, Dr. (Universiti Malaysia Perlis (UniMAP), 2012)
International Postgraduate Conference On Engineering (IPCE 2010), 16th - 17th October 2010 organized by Centre for Graduate Studies, Universiti Malaysia Perlis (UniMAP) at School of Mechatronic Engineering, Pauh Putra Campus, Perlis, Malaysia.